PENGARUH KOMUNIKASI DAN KERJASAMA TIM TERHADAP PENINGKATAN KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KABUPATEN BIMA - Nurradatul Nurradatul; Jaenab Jaenab; Kartin Aprianti (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of communication and teamwork on improving employee performance at the Bima Regency Transportation Agency. The type of research used is associative research with a quantitative approach. The sample in this study were all employees and P3k totaling 65 people, with a sample of 45 ASN employees and 20 P3k employees determined using purposive sampling. Data collection techniques used observation, questionnaires, and literature studies, while data analysis was carried out through validity tests, reliability tests, class assumption tests, multiple linear regression, correlation tests, determination coefficient tests, t tests and F tests. The results of the study indicate that 1) Communication has a significant effect on improving Employee Performance at the Bima Regency Transportation Agency, 2) Teamwork has a significant effect on improving employee performance at the Bima Regency Transportation Agency, 3) Communication and teamwork simultaneously have a significant effect on improving employee performance at the Bima Regency Transportation Agency.